The Effect of Applying a Developed Disaster Risk Reduction Guideline on Governmental Primary School Student’s Safety Behaviors - Alexandria Governorate, Egypt - Sherbini, Hanan Hosni El-; Badawy, Shaymaa Saeed Mohamed; Mohammed, Neama Yousef; Toama, Zakia Toma Yousef (International Journal For Research In Health Sciences And Nursing, 2020)
Abstract: Background: Each year, schools all over the world suffer from disasters, ranging from small to large damaging disasters that affect children safety and health. Disaster Risk Reduction (DRR) is a systematic approach to identify, assess and reduce disaster related risk. Children participation in such program enabling them to be positive change makers in their communities. Aims: this study to develop a disaster risk reduction guideline for governmental primary schools students and to assess the effect of applying developed disaster risk reduction guideline on safety behavior of governmental primary schools student in Alexandria/ Egypt. Design: A quasi experimental study design was adopted to carry out this study. Setting: the study was carried out in four primary schools of the educational zone in Alexandria governmental were selected randomly namely (El- Montazah and East zones). Subjects: 200 primary school students and 35 academic and field experts were selected. Tools: three tools were used; Tool (I) Primary school students’ disaster knowledge questionnaire, tool (II) Disaster risk reduction observation checklist, and tool (III) Guideline revision and evaluation of internal validation "AGREE II Instrument. Results: The findings of the present study revealed that the implementation of disaster risk reduction guideline training program leads to improved total knowledge and practice score among the studied students. Recommendations: Developing comprehensive coordination and cooperation agreements between educational institutions and civil society organizations to raise student's awareness about disaster risk reduction and its consequences. Revise curricular materials concerning crisis and disasters management to include all recent information on crises and disaster risk reduction in the schools, and methods of dealing with it. Use mass media to provide more information about safety and disaster management in radio, television, social media and in school curriculum. Distribute media as videos or computers applications for better clarification on disaster crisis management at school. Provide booklet explaining the safety, security & evacuation procedures in effective manner and meet the student's development stage. Provide school approval to do fieldtrip to civil protection, firefighting department and Red Cross/Red Crescent Society.